The Effect of Library Promotion Through Instagram Social Media on the Utilization of the Medan Stipap Library - Sidabutar, Widiya Kasih (Pena Cendekia Insani, 2022)
This study aims to determine the description of the variables and the effect of promotion through Instagram on library utilization. Instagram is the most influential social media in library promotion because Instagram is easily accessible by anyone and is usually owned by everyone, business entities and certain organizations. The respondents in this research amounted to 76 people. This type of research uses an explanatory research method with a quantitative approach using simple linear analysis and descriptive statistical analysis as a statistical measurement tool with the SPSS version 20 software application. The methods of data collection uses questionnaires and literature study. The results of this research indicate that promotion throught Instagram has an effect on library utilization at the STIPAP Medan Library.